Managing to Stay in the Dark: Managerial Self-Efficacy, Ego Defensiveness, and the Aversion to Employee Voice - Fast, Nathanael J.; Burris, Ethan R.; Bartel, Caroline A. (Academy of Management Journal, 2014)
Soliciting and incorporating employee voice is essential to organizational performance, yet some managers display a strong aversion to improvement-oriented input from subordinates. To help to explain this maladaptive tendency, we tested the hypothesis that managers with low managerial self-efficacy (that is, low perceived ability to meet the elevated competence expectations associated with managerial roles) seek to minimize voice as a way of compensating for a threatened ego. The results of two studies support this idea. In a field study (Study 1), managers with low managerial self-efficacy were less likely than others to solicit input, leading to lower levels of employee voice. A follow-up experimental study (Study 2) showed that: (a) manipulating low managerial self-efficacy led to voice aversion (that is, decreased voice solicitation, negative evaluations of an employee who spoke up, and reduced implementation of voice); and (b) the observed voice aversion associated with low managerial self-efficacy was driven by ego defensiveness. We discuss the theoretical and practical implications of these findings, as well as highlight directions for future research on voice, management, and leadership.